Spatiotemporal Differences and Spatial Convergence of the Water-Energy-Food-Ecology Nexus in Northwest China - Wang, Min; Zhu, Yi-fei; Gong, Si-wen; Ni, Chang-yu (Frontiers in Energy Research, 2021)
The Water-Energy-Food-Ecology (W-E-F-E) nexus is related to the realization of the goal of high-quality economic development in Northwest China. This paper analyzed the dynamic change trend, spatial evolution characteristics, and spatial convergence of identified W-E-F-E nexus in Northwest China utilizing the coupling coordination degree model, an ESDA instrument, and the spatial convergence model. The results show that: first, the W-E-F-E nexus in Northwest China presents a “V” shaped trend of decreasing first and then rising in time dimension. After a decline of 25.1% in 2002–2012, it increased by 29.7% in 2012–2017. Second, the W-E-F-E nexus in Northwest China shows positive spatial autocorrelation, and the Moran’s I index of this is about 0.15. In spatial dimension, it shows a trend of high-value agglomeration around provincial capitals, and the distribution pattern is relatively stable. Thirdly, the W-E-F-E nexus in Northwest China has significant spatial convergence, that is, the W-E-F-E nexus gap between the prefectures in Northwest China is shrinking, and the convergence rate is between 2.83 and 3.16. Moreover, with the development of the economy, the rational allocation of land and labor resources, and the optimization of fiscal expenditure structure, the W-E-F-E nexus in Northwest China will converge to the same steady state level after a long period of time. In general, in the process of improving the W-E-F-E nexus in Northwest China, the heterogeneous characteristics of prefectures should be fully considered, and a trans-regional cooperative management and restriction mechanism of the W-E-F-E nexus should be explored to achieve high-quality development of the region.